The Effect of Oxytocin Massage on Breast Milk Production in Postpartum Mothers at Sidamulya Health Center Cirebon Regency - Khulaili, Barkah; Mutya Sari, Vianty; Aliah, Nur; Difta R, Siti (Ann Publisher, 2023)
Exclusive breastfeeding affects the quality of the baby's health. But in practice, it is still relatively low. Data from the Puskesmas in 2022 achieved 55% exclusive breastfeeding and 48% achievement of exclusive breastfeeding in Sidamulya village. Low coverage of exclusive breast milk can be done by stimulating production. Oxytocin massage is one solution to overcome the smooth production of breast milk (ASI). The purpose of this study was to determine the effect of oxytocin massage to increase breast milk production in postpartum mothers at Sidamulya Health Center, Astanajapura District, Cirebon Regency. Quasi-experimental research method with pretest and posttest approach without control group. The sample of this study was 20 people who were postpartum mothers for 7-9 days at Puskesmas Sidamulya, Astanajapura District, Cirebon Regency in April – June 2023 with Total Sampling techniques. Data were analyzed using univariate analysis of frequency distribution and bivariate analysis of t-test. Univariate results of breast milk production in postpartum mothers before oxytocin massage on average day 1 = 40,625 ml, day 2 = 50,300 ml, day 3 = 57,725 ml, after oxytocin massage average day 1 = 48,025 ml, day 2 = 56,675 ml, day 3 = 63,375 ml. The paired simple t test results obtained p value = 0.000. There is an effect of oxytocin massage on milk production. It is hoped that the family can motivate the mother in the breastfeeding process by giving oxytocin massage so that the mother can exclusively breastfeed her.